Fusion Hindrance and Pauli Blocking in 58Ni + 64Ni. (December 2020) - Stefanini, A.M.; Montagnoli, G.; Fabbro, M. Del; Colucci, G.; Čolović, P.; Corradi, L.; Fioretto, E.; Galtarossa, F.; Goasduff, A.; Grebosz, J.; Heine, M.; Jaworski, G.; et al.
Abstract: 58 Ni + 64 Ni is the first case where the influence of positive Q-value transfer channels on sub-barrier fusion was evidenced, in a very well known experiment by Beckerman et al., by comparing with the two systems 58 Ni + 58 Ni and 64 Ni + 64 Ni. Subsequent measurements on 64 Ni + 64 Ni showed that fusion hindrance is clearly present in this case. On the other hand, no indication of hindrance can be observed for 58 Ni + 64 Ni down to the measured level of 0.1 mb. In the present experiment the excitation function has been extended by two orders of magnitude downward. The cross sections for 58 Ni + 64 Ni continue decreasing very smoothly below the barrier, down to ≃1 μ b. The logarithmic slope of the excitation function increases slowly, showing a tendency to saturate at the lowest energies. No maximum of the astrophysical S -factor is observed. Coupled-channels (CC) calculations using a Woods-Saxon potential and including inelastic excitations only, underestimate the sub-barrier cross sections by a large amount. Good agreement is found by adding two-neutron transfer couplings to a schematical level. This behaviour is quite different from what already observed for 64 Ni+ 64 Ni (no positive Q -value transfer channels available), where a clear low-energy maximum of the S -factor appears, and whose excitation function is overestimated by a standard Woods-Saxon CC calculation. No hindrance effect is observed in 58 Ni+ 64 Ni in the measured energy range. This trend at deep sub-barrier energies reinforces the recent suggestion that the availability of several states following transfer with Q >0, effectively counterbalances the Pauli repulsion that, in general, is predicted to reduce tunneling probability inside the Coulomb barrier.